2020
DOI: 10.1039/d0cp01291b
|View full text |Cite
|
Sign up to set email alerts
|

A new tuned range-separated density functional for the accurate calculation of second hyperpolarizabilities

Abstract: Among the nine functionals benchmarked, the most accurate γ are obtained by Tα-LC-BLYP, reducing about half the errors of LC-BLYP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 62 publications
4
56
0
Order By: Relevance
“…DFAs with a low percentage of Hartree–Fock (HF) exchange (typically, HF[%]≪50) at long interelectronic ranges are prone to present large delocalization errors, [27] leading to the unphysical overdelocalization of electrons, the underestimation of reaction barriers and charge‐transfer excitation energies, [27] the overestimation of the conductance of molecular junctions, optical responses,[ 28 , 29 ] the magnetizability of strong antiaromatic molecules, [30] electron conjugation, [31] and aromaticity,[ 32 , 33 ] especially in large conjugated macrocycles. [ 2 , 3 , 34 , 35 , 36 , 37 ] Anderson et al.…”
Section: Resultsmentioning
confidence: 99%
“…DFAs with a low percentage of Hartree–Fock (HF) exchange (typically, HF[%]≪50) at long interelectronic ranges are prone to present large delocalization errors, [27] leading to the unphysical overdelocalization of electrons, the underestimation of reaction barriers and charge‐transfer excitation energies, [27] the overestimation of the conductance of molecular junctions, optical responses,[ 28 , 29 ] the magnetizability of strong antiaromatic molecules, [30] electron conjugation, [31] and aromaticity,[ 32 , 33 ] especially in large conjugated macrocycles. [ 2 , 3 , 34 , 35 , 36 , 37 ] Anderson et al.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the functional, CAM-B3LYP is a range-separated hybrid functional which adds long-range correction using the Coulomb-attenuating method and includes 19% of HF exchange at short-range and 65% at long-range 64 . It is expected to provide reliable results for the non linear optical properties of mediumsize molecules 72,73 . While it is true that DFT/CAM-B3LYP is not very accurate to compute cross section at resonant frequency 74 , the present work investigates SHG response for the fundamental frequency of 800 nm, i.e.…”
Section: Hyperpolarizability Calculationsmentioning
confidence: 99%
“…Finally, since the QM/MM approach involves an electrostatic environment, the second hyperpolarizability γ plays an important role. Besalú-Sala et al have showed recently that CAM-B3LYP is among the best choices regarding the second hyperpolarizability of water 73 .…”
Section: Hyperpolarizability Calculationsmentioning
confidence: 99%
“…DFAs with al ow percentage of Hartree-Fock (HF) exchange (typically,H F[%] ! 50) at long interelectronic ranges are prone to present large delocalization errors, [27] leading to the unphysical overdelocalization of electrons, the underestimation of reaction barriers and charge-transfer excitation energies, [27] the overestimation of the conductance of molecular junctions,o ptical responses, [28,29] the magnetizability of strong antiaromatic molecules, [30] electron conjugation, [31] and aromaticity, [32,33] especially in large conjugated macrocycles. [2,3,[34][35][36][37] Anderson et al [9] performed B3LYP (HF[%] = 19), M06-2X (HF[%] = 54), and wB97X (HF[%] = 0-100) calculations with the 6-31G* basis set but mostly employed the B3LYP results to analyze the aromaticity of these compounds.W ehave performed additional calculations with CAM-B3LYP (HF[%] = 19-65) and LC-wHPBE (HF-[%] = 0-100), w being 0.1 and 0.2 (the larger w,t he larger HF[%] at long range).…”
Section: Resultsmentioning
confidence: 99%